2021
DOI: 10.1186/s12884-021-03673-0
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and intimate partner violence against pregnant women living with HIV in Cameroon: a cross-sectional analysis

Abstract: Background Women living with HIV are at increased risk of poor mental health and intimate partner violence (IPV). Mental health disorders have been consistently associated with suboptimal HIV-related outcomes. Little is known about the prevalence or correlates of mental health disorders among pregnant women living with HIV in sub-Saharan Africa. Methods This study assessed the prevalence of probable common mental disorders (CMD), i.e., depressive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Over 40% of respondents reported physical assault by a partner and 26% reported sexual violence in adulthood. This is similar to a meta-analysis which found that 33% of PWH in sub-Saharan Africa reported having experienced IPV and to a study of pregnant women living with HIV in Cameroon in which 37% reported physical IPV and 31% reported sexual IPV [9,10]. HIV-related stigma is often a direct or indirect cause of violence against PWH and has been consistently associated with poor mental health.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Over 40% of respondents reported physical assault by a partner and 26% reported sexual violence in adulthood. This is similar to a meta-analysis which found that 33% of PWH in sub-Saharan Africa reported having experienced IPV and to a study of pregnant women living with HIV in Cameroon in which 37% reported physical IPV and 31% reported sexual IPV [9,10]. HIV-related stigma is often a direct or indirect cause of violence against PWH and has been consistently associated with poor mental health.…”
Section: Resultssupporting
confidence: 84%
“…However, a meta-analysis estimated that 33% of women with HIV in SSA have experienced IPV [9]. Other studies have reported substantially higher prevalence of IPV among women with HIV across global settings [10,11]. For example, a study of women with HIV in South Africa found that 81% of respondents reported having experienced physical or sexual IPV in their lifetime [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 32 included studies, the majority were conducted among people living with HIV, [12][13][14][15][16][17][18][19][20][21][22][23][24] followed by students, [25][26][27][28][29][30] hospital patients (including patients with diabetes, cancer and tuberculosis), [31][32][33][34] pregnant and postpartum women, 15 35 36 general population, 37 female sex workers 38 and children 38 39 (online supplemental table 2)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Furthermore, HIV care engagement is disproportionately affected by mental health disorders, which are in turn frequently associated with IPV. Mental health disorders include IPV trauma, posttraumatic stress disorder (PTSD), and depression [81]. IPV has been linked with suboptimal HIV treatment outcomes such as antiretroviral therapy (ART) discontinuity [82], poor ART adherence 6 [53], and lack of viral suppression among women [83].…”
Section: Ipv and Hiv-positive Black Womenmentioning
confidence: 99%